Role of Biomarkers in the Clinical Management of Glioblastomas: What are the Barriers and How Can We Overcome Them? - Mcdonald, Kerrie L.; Aw, Grace; Kleihues, Paul (Frontiers in Neurology, 2013)
Thousands of articles describing biomarkers predictive of treatment and prognostic of survival in cancer have been published, yet only a handful of biomarkers are currently used routinely in the clinic. Biomarkers need to be analytically standardized, validated, and clinically useful. This review will address the challenges and ways in which we can improve our discovery and translation of prospective biomarkers from the lab into validated diagnostic tests with a specific focus on patients diagnosed with glioblastoma and MGMT promoter methylation status. There has been long-held enthusiasm to use MGMT promoter methylation as a predictive biomarker for patients treated with the alkylating agent, temozolomide; however in the majority of centres around the world, this has not yet transpired.